PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP NILAI PERUSAHAAN SEBELUM DAN SAAT PANDEMI - Feny Nofiasti (2023)
This study aims to analyze the influence of internal factors and external factors on the value of telecommunications sub-sector companies in conditions before and during the pandemic. This study applies two models that were tested with coefficients during the pandemic and before the pandemic with saturated sample data, namely 5 telecommunications companies with an eight-year research period and obtained 40 sample units. Data analysis in the study used Microsoft Excel, hypothesis testing and Difference Test used Panel Data Regression Analysis with the E-Views 12 program and a significance level of 5%. The results of this study indicate that there were no differences in Investment Decisions and Capital Structure before and during the pandemic. Investment Decision (CPABVA) has no effect on Firm Value (PBV) with a coefficient during a pandemic. Capital Structure (DER), Interest Rates and Inflation affect company value with a coefficient during a pandemic. Investment Decision (CPABVA) and Capital Structure (DER) have an effect on company value with a pre-pandemic coefficient. Inflation and interest rates have no effect on firm value with the pre-pandemic coefficient.Keywords: Firm Value, Investation decision, Capital Structure, Interest Rate, and Inflation.